Association between allergic diseases and mucosal healing in ulcerative colitis - Yasunori Yamamoto; Shinya Furukawa; Osamu Yoshida; Teruki Miyake; Kana Shiraishi; Yu Hashimoto; Kazuhiro Tange; Shogo Kitahata; Tomoyuki Ninomiya; Sen Yagi; Hanayama Masakazu; Seiyuu Suzuki; et al. (Scientific Reports)
Abstract Allergic diseases and ulcerative colitis (UC) share pathophysiological similarities. This study aimed to investigate the unclear association between allergic diseases and mucosal healing (MH), an important factor in the prognosis of UC. We studied 289 Japanese patients with UC. Information on allergic diseases (bronchial asthma, atopic dermatitis, pollen allergy, food allergy, and drug allergy), as diagnosed by physicians, was collected through self-reported questionnaires. The definition of MH was Mayo Endoscopic Score 0. The association between each allergic disease and its multimorbidity with MH was evaluated using multivariate logistic regression analyses. Pollen allergy was the most common allergic condition (36.3%). Pollen allergy and food allergy were independently associated with MH (pollen allergy adjusted OR: 1.82 [95% CI: 1.01–3.26]; food allergy adjusted OR: 3.47 [95% CI: 1.26–9.68]). The rates of MH for 0 and 3 or more allergic diseases were 24.6% and 4.2%, respectively. After adjustment for confounders, 3 or more allergic diseases were independently associated with MH (adjusted OR: 8.13 [95% CI: 2.17–34.04], p for trend = 0.020). This study demonstrates a significant positive association between specific allergic diseases (pollen and food allergies) and MH in UC patients, with a stronger association in cases of allergic multimorbidity.